Enhanced magnetic properties in epitaxial self-assembled vertically aligned nanocomposite (Pr0.5Ba0.5MnO3)0.5:(CeO2)0.5 thin films. Issue 46 (11th November 2016) - Shen, Lvkang; Ma, Chunrui; Cheng, Shaodong; Ren, Shengping; Cheng, Sheng; Mi, Shaobo; Liu, Ming
Abstract : Magnetic properties are strongly enhanced in vertically aligned nanocomposite Pr0.5 Ba0.5 MnO3 :CeO2 films by introducing CeO2 into Pr0.5 Ba0.5 MnO3 matrix. Abstract : Epitaxial self-assembled vertically aligned nanocomposite (VAN) Pr0.5 Ba0.5 MnO3 :CeO2 (PBMO:CeO2 ) and pure PBMO films were fabricated on (001) (La, Sr)(Al, Ta)O3 substrates by pulsed laser deposition. Besides confirmation of the in-plane and out-of-plane orientations using X-ray diffraction, transmission electron microscopy study has revealed the columnar structure of PBMO:CeO2, with column width around 10–20 nm; furthermore, energy dispersive X-ray spectroscopy has revealed distinct phase separation between PBMO and CeO2 . The introduction of CeO2 does not change the crystal quality of PBMO, and both films exhibit good crystalline quality. However, the vertical compressive strain induced by CeO2 partially relaxes the in-plane and out-of-plane strain of PBMO relative to the pure film. The magnetization of the VAN thin film is enhanced and almost two times higher than that of the pure film. Moreover, the relaxed strain and the insulating CeO2 nanopillar act as an energy barrier to induce the larger resistivity and enhanced magneto-resistance. All of these phenomena indicate that the VAN structure is an effective method to tune the strain states in thin films and obtain desired physical properties.